The Global Information and Communications Technology Industry : Where Vietnam Fits in Global Value Chains - Sturgeon, Timothy (World Bank, Washington, DC, 2017)
The information and communications technology sector has undergone a dynamic process of globalization and fragmentation in the past few decades, leading to the creation of global value chains. Global value chains are populated by a constellation of specialized actors collectively responsible for bringing goods and services to market. Most prominently, these key actors include lead firms (brands), contract manufacturers, platform leaders, and increasingly, information and communications technology services and information and communications technology-enabled services providers. Like other emerging markets, Vietnam is coming to play an important role in this global industry. The recent influx of foreign investors, driven by the country's low wages and easy access to regional supply chains, as well as the emergence of various local information and communications technology services and information and communications technology–enabled services firms opens opportunities, yet raises important questions for policy makers about how best to leverage global engagement for local capacity building. This paper situates Vietnam in the global information and communications technology industry, and identifies several constraints to future growth, including the limited availability and quality of trained information and communications technology professionals, ineffective supplier development initiatives, and weak entrepreneurial ecosystem, especially in management skills. The paper concludes with a set of policy recommendations and forward-looking statements aimed at helping Vietnam move into higher-value activities in the coming years. The analysis is based on relevant statistics published by the United Nations, Organisation for Economic Co-operation and Development, World Trade Organization, Government of Vietnam, and Vietnamese industry associations, as well as interviews and site visits conducted by the authors during January 19-30, 2015.